Pendampingan Industri Kreatif pada Usaha Kecil Menengah (UKM) di Sentra Pengrajin Dompet “Macakal” Guna Meningkatkan Daya Saing Pasar di Kabupaten Lebak Provinsi Banten - Mislan Mislan; Lucky Setiawan; Ari Handoko; Dedy Khaerudin; Irma Nurmala Dewi (Universitas Kristen Indonesia Toraja, 2025)
The contribution of artisans to the enhancement of the economy in Indonesia, particularly within the home industry sector of small and medium enterprises (SMEs) located in the